2016
DOI: 10.1016/j.celrep.2015.12.043
|View full text |Cite
|
Sign up to set email alerts
|

Deposition of 5-Methylcytosine on Enhancer RNAs Enables the Coactivator Function of PGC-1α

Abstract: SUMMARY The Peroxisome proliferator-activated receptor-gamma coactivator 1 alpha (PGC-1α) is a transcriptional co-activator that plays a central role in adapted metabolic responses. PGC-1α is dynamically methylated and unmethylated at the residue K779 by the methyltransferase SET7/9 and the Lysine Specific Demethylase 1A (LSD1), respectively. Interactions of methylated PGC-1α[K779me] with the Spt-Ada-Gcn5-acetyltransferase (SAGA) complex, the Mediator members MED1 and MED17, and the NOP2/Sun RNA methytransfera… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
104
0

Year Published

2016
2016
2023
2023

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 138 publications
(106 citation statements)
references
References 54 publications
2
104
0
Order By: Relevance
“…This observation raises the possibility that m5C may be involved in the splicing process or may mark transcripts for degradation. Another intriguing possibility is that m5C may decorate regulatory RNAs, such as promoter- or enhancer-derived transcripts [43], which was indeed demonstrated by Aguilo et al in a recent work [44]. …”
Section: Discussionmentioning
confidence: 99%
“…This observation raises the possibility that m5C may be involved in the splicing process or may mark transcripts for degradation. Another intriguing possibility is that m5C may decorate regulatory RNAs, such as promoter- or enhancer-derived transcripts [43], which was indeed demonstrated by Aguilo et al in a recent work [44]. …”
Section: Discussionmentioning
confidence: 99%
“…One explanation for their complex biology might be that these MTases modify additional substrates outside of the tRNA and rRNA realm. Indeed, NSUN7 was recently identified as a modifier of enhancer RNAs [44], but NSUN2 has also repeatedly been found to methylate sites outside of its purview [9,[45][46][47][48][49][50]. Two 'readers' of m 5 C have been reported, the mRNA export adapter ALYREF (Aly/REF export factor) [49] and the DNA/RNA-binding protein YBX1 (Y-box binding protein 1) [47,51], implying certain molecular functions (see below).…”
Section: Introductionmentioning
confidence: 99%
“…One explanation for their complex biology might be that these MTases modify additional substrates outside of the tRNA and rRNA realm. Indeed, NSUN7 was recently identified as a modifier of enhancer RNAs (Aguilo et al 2016), but NSUN2 has also repeatedly been found to methylate sites outside of its purview (Squires et al 2012;Hussain et al 2013b;Khoddami and Cairns 2013;Yang et al 2017;Chen et al 2019;Huang et al 2019;Sun et al 2019). Two 'readers' of m 5 C have been reported, the mRNA export adapter ALYREF (Aly/REF export factor) (Yang et al 2017) and the DNA/RNAbinding protein YBX1 (Y-box binding protein 1) Yang et al 2019b), implying certain molecular functions (see below).…”
Section: Introductionmentioning
confidence: 99%